Flavogenomics: a genomic and structural view of flavin-dependent proteins - Macheroux, Peter; Kappes, Barbara; Ealick, Steven E. (The FEBS journal, 2011)
Riboflavin (vitamin B2) serves as the precursor for FMN and FAD in almost all organisms that utilize the redox-active isoalloxazine ring system as a coenzyme in enzymatic reactions. The role of flavin, however, is not limited to redox processes, as ∼ 10% of flavin-dependent enzymes catalyze nonredox reactions. Moreover, the flavin cofactor is also widely used as a signaling and sensing molecule in biological processes such as phototropism and nitrogen fixation. Here, we present a study of 374 flavin-dependent proteins analyzed with regard to their function, structure and distribution among 22 archaeal, eubacterial, protozoan and eukaryotic genomes. More than 90% of flavin-dependent enzymes are oxidoreductases, and the remaining enzymes are classified as transferases (4.3%), lyases (2.9%), isomerases (1.4%) and ligases (0.4%). The majority of enzymes utilize FAD (75%) rather than FMN (25%), and bind the cofactor noncovalently (90%). High-resolution structures are available for about half of the flavoproteins. FAD-containing proteins predominantly bind the cofactor in a Rossmann fold (∼ 50%), whereas FMN-containing proteins preferably adopt a (βα)8-(TIM)-barrel-like or flavodoxin-like fold. The number of genes encoding flavin-dependent proteins varies greatly in the genomes analyzed, and covers a range from ∼ 0.1% to 3.5% of the predicted genes. It appears that some species depend heavily on flavin-dependent oxidoreductases for degradation or biosynthesis, whereas others have minimized their flavoprotein arsenal. An understanding of ‘flavin-intensive’ lifestyles, such as in the human pathogen Mycobacterium tuberculosis, may result in valuable new intervention strategies that target either riboflavin biosynthesis or uptake.